(untitled) (Communications in Mathematical Research, 2020)
In this paper, we consider the 2-D MHD equations with magnetic resistivity but without dissipation on the torus. We prove that if the initial data is small in H^4(T^2), then the 2-D MHD equations are globally well-posed. To our knowledge, this is the first global well-posedness result for this system.